2020
DOI: 10.31234/osf.io/vtbr7
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Applying the technology acceptance model to digital mental health interventions: a qualitative exploration with adults with intellectual disabilities

Abstract: Introduction: Digital mental health interventions are on the rise; yet people with intellectual disabilities are not generally seen as their potential users. This study aims to explore the accessability of two mainstream online mood-management programmes.Methods: Using a qualitative study design, 12 adults with intellectual disabilities were interviewed while accessing moodgym and iFightDepression®. Thematic analysis was used to explore the programs’ accessibility according to the technology acceptance model. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…On the other hand, self-efficacy was found to be a strong factor in the adoption of technology by individuals with orthopedic disabilities (Cho & Lee, 2020). It has been stated that the usefulness of the relevant technology, ease of use, in other words, accessibility for the sense of hearing and vision are the most important factors in the use of technology and feeling self-sufficient in individuals with hearing and vision impairments (Vereenooghe et al, 2020).…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…On the other hand, self-efficacy was found to be a strong factor in the adoption of technology by individuals with orthopedic disabilities (Cho & Lee, 2020). It has been stated that the usefulness of the relevant technology, ease of use, in other words, accessibility for the sense of hearing and vision are the most important factors in the use of technology and feeling self-sufficient in individuals with hearing and vision impairments (Vereenooghe et al, 2020).…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…These findings indicate that the beliefs of students with disability in their own knowledge and skills in the context of performing a task using technology influence their perceptions of the performance increase they will achieve by using technology and their intention to continue using information technologies. It has been stated that the perceived usefulness and ease of use affect adopting digital mental health applications for intellectual disability (Vereenooghe et al, 2020). It was concluded that hearing loss alone does not have an effect on academic achievement in hearing impaired students who continue distance education, but additional disabilities and severe hearing impairment have a negative effect on the academic performance of students (Richardson, 2015).…”
Section: Introductionmentioning
confidence: 99%